Analisis Faktor-Faktor yang Mempengaruhi Kepuasan Jamaah Umroh PT. Lianti Tour & Travel di Kota Malang - Trian Maulana Ibrahim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to identify the factors influencing pilgrims’ satisfaction at PT. Lianti Tour & Travel in Malang City, with service quality as an intervening variable. The research employed a quantitative approach using Partial Least Square (PLS) analysis. The sample consisted of Umrah pilgrims who had used PT. Lianti Tour & Travel’s services. The variables examined include price, income, preference, facilities, service quality, and customer satisfaction. The results indicate that price and income have no significant effect on service quality or customer satisfaction. Likewise, facilities do not significantly influence either variable. In contrast, preference has a positive and significant effect on service quality and indirectly influences satisfaction through the mediating role of service quality. The findings highlight that service quality has a strong and significant impact on customer satisfaction, making it the key factor in creating a fulfilling Umrah experience. This research implies that Umrah travel agencies should prioritize improving service quality and understanding customer preferences to maintain loyalty and trust among pilgrims in the long term.